2016
DOI: 10.3892/ol.2016.4580
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CCAT2 functions as an oncogene in hepatocellular carcinoma, regulating cellular proliferation, migration and apoptosis

Abstract: An increasing number of studies have demonstrated that the dysregulation of long non-coding RNAs (lncRNAs) may serve an important role in tumor progression. Previous studies have reported that the lncRNA, colon cancer associated transcript 2 (CCAT2), was highly expressed in various tumors. However, the function of CCAT2 in hepatocellular carcinoma (HCC) has not yet been elucidated. The aim of the present study was to identify novel oncogene lncRNAs and investigate their physiological function and mechanism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Several lncRNAs, including LINC00152, GHET1, HULC, HOTAIR, GACAT3, MALAT2 and H19, have been demonstrated to serve as oncogenes, whereas other lncRNAs, including LEIGC, GAS5 and FER1L4, have been considered to be tumor suppressors (10). Emerging evidence indicated that CCAT2 functions as a cancer-promoting molecule in several types of solid cancer, such as in non-small cell lung cancer (11), oral squamous cell carcinoma (12), ovarian cancer (13), and hepatocellular carcinoma (14). The present study investigated the effects of the lncRNA CCAT2 on the biological behavior of BGC-823 cells, and revealed that knockdown of CCAT2 expression effectively inhibited the proliferation, as well as induced the apoptosis and autophagy of GC cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNAs, including LINC00152, GHET1, HULC, HOTAIR, GACAT3, MALAT2 and H19, have been demonstrated to serve as oncogenes, whereas other lncRNAs, including LEIGC, GAS5 and FER1L4, have been considered to be tumor suppressors (10). Emerging evidence indicated that CCAT2 functions as a cancer-promoting molecule in several types of solid cancer, such as in non-small cell lung cancer (11), oral squamous cell carcinoma (12), ovarian cancer (13), and hepatocellular carcinoma (14). The present study investigated the effects of the lncRNA CCAT2 on the biological behavior of BGC-823 cells, and revealed that knockdown of CCAT2 expression effectively inhibited the proliferation, as well as induced the apoptosis and autophagy of GC cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have indicated that dysregulation of lncRNA involved in the biologic processes of tumor [ 21 ]. In HCC, Long non-coding RNA CCAT2 functions as an oncogene in hepatocellular carcinoma, regulating cellular proliferation, migration and apoptosis [ 22 ]. LncRNA HULC enhances epithelial-mesenchymal transition to promote tumorigenesis and metastasis of hepatocellular carcinoma via the miR-200a-3p/ZEB1 signaling pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that CCAT2 gene may act as a novel oncogene in these tumors,regulating celluar growth,migration and apoptosis. Moreover, abnormal expression of CCAT2 was suggested to be associated with lymph node metastasis,distant metastasis and overall survival [ 17 ] . Therefore, we performed this meta-analysis to investigate the lymph node metastasis, distant metastasis and clinical prognostic role of overexpression CCAT2 in human cancers.…”
Section: Introductionmentioning
confidence: 99%